The eagle on my arm : how the wilderness and birds of prey saved a veteran's life - Guerin, Dava; Bivens, Terry (American warriors, 2020)
"In October 1967, eighteen-year-old Patrick Bradley enlisted in the US Army and was later deployed to North Vietnam as a special operator with missions to kill high-value targets. Combat left him physically and psychologically wounded, as it does many veterans, and Bradley struggled to adjust when he returned home. He seemed destined for military prison after an altercation in which he broke a superior officer's jaw, but his life changed forever when a psychiatrist recommended a unique path for healing. Thanks to a program sponsored by the Canadian government, Bradley traveled to Canada to study bald eagles and document their behavior. He found himself recovering while living alone in the wild with minimal supplies or human contact. At the same time, his work was paving the way for groundbreaking research, including the discovery of a link between the use of the pesticide DDT and a decrease in southern bald eagle populations. Later, he forged a successful career training and managing wild animals and committed himself to helping other wounded warriors by cofounding the Avian Veteran Alliance, a nonprofit that pairs veterans suffering from PTSD and physical injuries with injured birds of prey. The Eagle on My Arm tells Bradley's inspirational story for the first time. This moving account reveals how a soldier became a dedicated healer, using his years of study and solitude to face his demons and turn his pain into a lifelong passion for helping others."--